Genesis, Evolution and Prevalence of H5N6 Avian Influenza Viruses in China - Bi, Yuhai; Chen, Quanjiao; Wang, Qianli; Chen, Jianjun; Jin, Tao; Wong, Gary; Quan, Chuansong; Liu, Jun; Wu, Jun; Yin, Renfu; Zhao, Lihua; Li, Mingxin; et al. (Cell host & microbe, 2016)
Constant surveillance of live poultry markets (LPMs) is currently the best way to predict and identify emerging avian influenza viruses (AIVs) that pose a potential threat to public health. Through surveillance of LPMs from 16 provinces and municipalities in China during 2014-2016, we identified 3,174 AIV-positive samples and isolated and sequenced 1,135 AIVs covering 31 subtypes. Our analysis shows that H5N6 has replaced H5N1 as one of the dominant AIV subtypes in southern China, especially in ducks. Phylogenetic analysis reveals that H5N6 arose from reassortments of H5 and H6N6 viruses, with the hemagglutinin and neuraminidase combinations being strongly lineage specific. H5N6 viruses constitute at least 34 distinct genotypes derived from various evolutionary pathways. Notably, genotype G1.2 virus, with internal genes from the chicken H9N2/H7N9 gene pool, was responsible for at least five human H5N6 infections. Our findings highlight H5N6 AIVs as potential threats to public health and agriculture.